Pemanfaatan cerita rakyat sebagai media storynomics dalam pendidikan kejuruan pariwisata: Studi Di SMKN 1 Panggul - Divan Robi Pangestu; Dwi Purwanto; Fitri Amaliyah; Imam Suroso; Jihan Jannata Abdullah (SAP (Susunan Artikel Pendidikan), 2025)
This study aims to analyze the utilization of folklore as a storynomics in vocational tourism education, specifically at SMKN 1 Panggul, Trenggalek Regency. Folklore, as part of local wisdom, has the potential to enrich tourism learning with deep cultural values. Employing a descriptive qualitative- analytical approach and document study, this research, conducted in 2025, explores the integration of folklore from Babad Tanah Panggul (e.g., the tales of Mbah Panji Nawangkung, Kyai Onggo, and Nyi Rumbung) into the Vocational Tourism Services curriculum. The findings indicate that these folklores contain values such as leadership, mutual cooperation, resilience, and ethics, making them highly relevant for developing local culture-based tourism guiding competencies. This integration can enhance students' cultural literacy and character, while also contributing to the development of local wisdom- based tourism. The study also identifies implementation challenges,including limited documentation and teachers' preparedness. Therefore, teacher training and community collaboration are essential.